150k views
0 votes
I need help with any but 14. It’s trig identities

I need help with any but 14. It’s trig identities-example-1

1 Answer

6 votes
Short answer: 2

(Sin(x) - Cos(x) )^2 = sin^2(x) - 2 sin(x)*cos(x) + cos^2(x)
(sin(x) + cos(x) )^2 = sin^2(x) + 2sin(x)*cos(x) + cos^2(x) Add these two
2sin^2(x) + 2cos^2(x) is all that is left. The two middle terms cancel out

Take out the common factor of 2
2(sin^2(x) + cos^2(x) )
but sin^2(x) + cos^2(x) = 1

2 * 1 = 2
2 <<<< answer
User Kestasx
by
6.1k points